Crystallin Fusion Proteins Improve the Thermal Properties of Hair - Tinoco, Ana; Gonçalves, José; Silva, Carla; Cavaco-Paulo, Artur; Ribeiro, Artur (Frontiers in Bioengineering and Biotechnology, 2019)
Styling the hair with straightening irons is a popular daily hair routine that significantly damage the hair keratin fiber due to the high temperature application. In this study, we investigate the effect of two fusion proteins based on the human eye γD-crystallin conjugated with a keratin-based peptide (KP-Cryst Wt and KP-Cryst Mut) on hair exposed to thermal damage. The mutant form was designed to improve protein stability and promote interaction with the hair. Through the study, it was demonstrated the protection of Asian and Caucasian virgin hair’s structure by the pretreatments with the KP-Cryst fusion proteins. After hair thermal exposure, a higher water content was verified by TGA on the hair fibers pretreated with the proteins (about 38% for the KP-Cryst Wt and 44% for the KP-Cryst Mut). Also, negligible alterations in hair fibers’ stiffness were observed after iron application, demonstrating the proteins capacity to effectively prevent the conversion of keratin α-helix structure into β-sheets. The results proved the capacity of KP-Cryst fusion proteins to bind to hair and protect it against high temperatures’ procedures, and support the development of new formulations based on the KP-Cryst proteins, to protect hair from thermal damage.